Reading Ability and Strategies of Students in Coastal Area of Bengkulu - Jayanti, Fernandita Gusweni; Dewi, Anggun Citra Sari (Lingual Journal of Language and Culture, 2018)
The purpose of this study is to discuss students’ reading ability and the reading strategies they use when they read English texts. This study employs a descriptive-qualitative approach. The data were gained by using two instruments; a reading comprehension test and a questionnaire on reading strategy. The respondents of this research were 243 third year students from four senior high schools located in coastal area in Bengkulu city. The results of students’ reading comprehension test showed that the students’ reading ability is categorized as poor. This study also found that the students use reading strategies in medium frequency. It means that the students do not make use of reading strategies maximally. Furthermore, the analysis of the questionnaire also showed that the most frequently used strategies are finding the main idea of the text, guessing the meaning of difficult words and using background knowledge while reading, while the least frequently used strategies are looking at the text closely, finding specific information and interpreting graph, diagram and table. It is predicted that the students’ low reading ability was influenced by the way the students use reading strategy and the sociocultural factor of the students who live in coastal area.